Bailing Capsule combined with α-ketoacid tablets for stage 3 chronic kidney disease: Protocol of a double-blinded, randomized, controlled trial. Issue 20 (21st May 2021) - Hu, Xiuhong; Wang, Jing; Yang, Hongjuan; Ji, Suhua; Li, Yuhong; Xu, Baozhen; Cui, Hongrui
Abstract: Background: Chronic kidney disease (CKD) is a progressive and irreversible loss of kidney function. After stage 3, there will be increased risks of hypertension, heart failure, bone disease, anemia, gastrointestinal symptoms, and progression to end-stage kidney failure without proper intervention and treatment. Compound α-ketoacid tablets (KA) administration plays an important role in clinical CKD adjunctive therapy for patients with restricted protein intake. Bailing Capsule (BC), a commonly used Chinese patent medicine for renal diseases, could regulate human immune function, repair renal tubular epithelial cells, prevent renal tubular atrophy, and reduce kidney damage to improve renal function. In this study, we try to conduct a double-blinded, randomized, controlled trial to observe the efficacy and safety of BC combined with KA in treating patients with stage 3 CKD. Methods: This is a double-blinded, randomized, controlled trial. Patients will be randomly divided into treatment group (BC and KT) and control group (BC-simulation and KT) in a 1:1 ratio according to random number table. The treatment course will be 8 weeks, and the changes of subjective symptoms, patient global assessment (PGA) scale, serum creatinine, cystatin C, and estimated glomerular filtration rate, all related adverse events, vital sign measurements, and physical examinations will be recorded. SPSS 21.0 will be used for data analysis. Conclusions: The results will show whether BC combined with KA could alleviate the symptoms of fatigue, anorexia, halitosis, nausea, itching, and edema, improve kidney function in patients with CKD at stage 3. Trial registration: OSF Registration number: DOI 10.17605/OSF.IO/24AJ7.